Quel devenir pour les projets de contournements autoroutiers des métropoles régionales françaises ? - Laurent Gatineau (Belgeo)
French major regional cities (Bordeaux, Toulouse, Rouen, Strasbourg) want to build ring roads, hardly a few years after having completed their bypasses. The latter, closer to dense zones, are indeed threatened with congestion under the double effect of the peripheral traffic growth linked to the expansion of urban areas, and the transfer of automotive flows of urban centres modified by trams. According to technicians, the achievement of such ring roads is required in order to keep the interurban transit moving freely while at the same time distancing these roads from the urban cores. Carried out by central administrations, such projects come up against strong local oppositions which deny their ability to fulfil the needs of mobility. Nevertheless, and in spite of the Grenelle of the Environment, these projects seem to have been relaunched today.